What Motivates Healthcare Professionals' Referrals to Chaplains, and How to Help Them Formulate Referrals that Accurately Reflect Patients' Spiritual Needs?. Issue 1 (2nd January 2020) - Poncin, Emmanuelle; Niquille, Brigitte; Jobin, Guy; Benaim, Charles; Rochat, Etienne
Abstract : As many hospitals lack standardized referral protocols for spiritual care, healthcare professionals' perceptions and preferences play an important role in their decisions to refer patients to chaplains. To better understand what motivates these professionals to refer patients and how they approach spiritual care, this article examines referral requests from twelve healthcare professionals to a chaplain at the Lausanne University Hospital Department of Physical and Rehabilitation Medicine. Comparative discourse analysis highlights that requests are largely driven by difficulties in patient-professional relationships. Yet, further interviews reveal that healthcare professionals construct spiritual care as a way to access patients' sense of identity and explore the meaning they give to their lives and experiences, for the benefit of both patients and professionals. The discussion considers how chaplains could help healthcare colleagues formulate referrals that accurately reflect patients' spiritual needs, thus improving the relevance and quality of spiritual care.